Effects of Glycyrrhizin (GL) Supplementation on Survival, Growth Performance, Expression of Feeding-Related Genes, Activities of Digestive Enzymes, Antioxidant Capacity, and Expression of Inflammatory Factors in Large Yellow Croaker (Larimichthys crocea) Larvae - Yuntao Wang; Wenxuan Xu; Jianmin Zhang; Jiahui Liu; Zhen Wang; Yongtao Liu; Kangsen Mai; Qinghui Ai (Aquaculture Nutrition)
A 30-day feeding trial was conducted to determine the effects of dietary glycyrrhizin (GL) on survival, growth performance, expression of feeding-related genes, activities of digestive enzymes, antioxidant capacity, and expression of inflammatory factors of large yellow croaker larvae with an initial weight of 3.78±0.27 mg. Four 53.80% crude protein and 16.40% crude lipid diets were formulated with supplementation of 0%, 0.005%, 0.01%, and 0.02% GL, respectively. Results indicated that larvae fed diets with GL had higher survival rate and specific growth rate than the control (P<0.05). Compared with the control, the mRNA expression of orexigenic factor genes including neuropeptide Y (npy) and agouti-related protein (agrp) were significantly increased in larvae fed the diet with 0.005% GL, while the mRNA expression of anorexigenic factor genes including thyrotropin-releasing hormone (trh), cocaine and amphetamine regulated transcript (cart), and leptin receptor (lepr) were significantly decreased in larvae fed the diet with 0.005% GL (P<0.05). The trypsin activity in larvae fed the diet with 0.005% GL was significantly higher than the control (P<0.05). The alkaline phosphatase (AKP) activity in larvae fed the diet with 0.01% GL was significantly higher than the control (P<0.05). A clear increase of total glutathione (T-GSH) content, activities of superoxide dismutase (SOD), and glutathione peroxidase (GSH-Px) was observed in larvae fed the diet with 0.01% GL compared with the control (P<0.05). Moreover, the mRNA expression of interleukin-1β (il-1β) and interleukin-6 (il-6) (proinflammatory genes) in larvae fed the diet with 0.02% GL were significantly lower than the control (P<0.05). In conclusion, the supplementation of 0.005% -0.01% GL could enhance the expression of orexigenic factor genes, activities of digestive enzymes and antioxidant capacity, ultimately improving the survival, and growth performance of large yellow croaker larvae.